Work rates in a wheelchair basketball game - Rupf, R.; Hathaway, C. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Work rates in wheelchair basketball have received little attention in the scientific literature. Average speeds and mobility movement remain the most studied parameters (Sporner et al, 2009; de Witte et al, 2015). However, how these metrics change over the course of the game remain unknown. The purpose of this study is to characterize the distance travelled, average speed, and high intensity efforts produced over the course of a wheelchair basketball game. Methods: Distance travelled (DIST) and average speed (V) for 12 players was determined over 4 games during a Paralympic qualifying event, using the Catapult ClearSky system. High intensity efforts (HIE) were counted when athletes reached speeds above 60% maximal speed. Video analysis was performed, using SportsCode to track the time of every possession (POSS), and when the game clock was running (CLOCK) or stopped (DEAD) for 4 quarters (Q1, Q2, Q3, Q4). Timeframes from Catapult and Clearsky were merged, and only information for athletes on the court at any one time were tracked. Values displayed are averages of the 5 players on court. One way ANOVA, t tests, and pearson correlations were used for statistical analysis. Results: Over the 4 games, DIST, V, and HIE was 5582 (328) m, 1.11 (0.03) m/s, and 273 (19) respectively. DIST is correlated to POSS (r=0.8,p<0.05), with average DIST per POSS equal to 37 (1) m. V and HIE was 100% and 180% greater during CLOCK than DEAD (p<0.05). V and HIE for each POSS was 1.41 (0.04) m/s and 2 (0.5) respectively. There was no difference from Q1 to Q4 for DIST, V, and HIE. The amount of time spent in CLOCK is 6% (p<0.05) lower than time spent in DEAD. Discussion: The total work rates of wheelchair basketball players is strongly correlated to the number of possessions during a game. Further, work rates are stable over each quarter, suggesting the team is able maintain consistent efforts over the course of a game. This may be a result of increased rest time, with most of the game duration occurring with the game clock stopped.